Teaching Strategies Applied by EFL Teachers at Inclusive Classroom: An Learning Experince Learnt from Inclusive Classes - Neliyam Tiraeni; Lalu Ari Irawan; Arif Rahman (Journal of Language and Literature Studies, 2024)
The term inclusion in the field of education is broadly defined as the incorporation of students with disabilities or those with special needs into general classrooms. In this regard, inclusive education represents a concept of education with the aim of fulfilling human rights in terms of education without any sense of discrimination. Therefore, this study aimed to explore the pedagogical strategies used by teachers to teach English in inclusive classrooms. This study applies a descriptive qualitative method embracing the data collection techniques; observation, interviewing, and note-taking. The subject of this research was English teachers in the 9th grade of SMP IT Al Qimah. To analyze the data from observation, and interview, this study used data condensation, data visualization, and conclusion/verification. The results of this study show that English teachers at the immersion level apply two strategies when teaching English: active learning strategy and cooperative learning strategy. The problem that teachers encounter is the difficulty in choosing learning materials and controlling students’ moods. To solve problems related to teaching English in inclusive classrooms, teachers should share and discuss with after-school teachers about students’ abilities and learning goals. In addition, to enrich skills and knowledge dealing with the problems in teaching English in inclusive classes, teachers need to read many reference materials. Based on the result of the study, it is suggested that the teacher provide a smart solution besides, only sharing with shadow teachers and finding out a lot of references dealing with teaching strategies for inclusive students. Those solutions provide teachers with a lot of new insight and creativity to overlook the problems.